HUBUNGAN KONSELING BERLANDASKAN “PEUMULIA JAMEE” (KEARIFAN LOKAL ACEH) - Zahra Nelissa; Sunaryo Kartadinata; Mamat Supriatna (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
“Peumulia Jamee” is one of an important elements in the foundation of the counseling relationship in Aceh. This article contains about the study of "Peumulia Jamee" in the context of Guidance and Counseling in the scope of education. As for this article aims to describe "Peumulia Jamee" about philosophical review and previous research trends comprehensively. The research method used is a qualitative research with a literature study research design. There is an integrated counseling relationship in "Peumulia Jamee" which can be used as the basis for Local Wisdom counseling. The results of this study are expected to contribute theoretically and practically in developing the expansion of the repertoire of scientific studies of guidance and counseling for Guidance and Counseling Teachers in Aceh